Advances in drug delivery applications of modified bacterial cellulose-based materials - Liang, Shuya (Frontiers in Bioengineering and Biotechnology, 2023)
Bacterial cellulose (BC) is generated by certain species of bacteria and comprises polysaccharides with unique physical, chemical, and mechanical characteristics. Due to its outstanding biocompatibility, high purity, excellent mechanical strength, high water absorption, and highly porous structure, bacterial cellulose has been recently investigated for biomedical application. However, the pure form of bacterial cellulose is hardly used as a biomedical material due to some of its inherent shortcomings. To extend its applications in drug delivery, modifications of native bacterial cellulose are widely used to improve its properties. Usually, bacterial cellulose modifications can be carried out by physical, chemical, and biological methods. In this review, a brief introduction to bacterial cellulose and its production and fabrication is first given, followed by up-to-date and in-depth discussions of modification. Finally, we focus on the potential applications of bacterial cellulose as a drug delivery system.